Pengaruh Model Pembelajaran Discovery Learning Menggunakan Alat Peraga Jam Baretika terhadap Pemahaman Konsep Siswa pada Materi Barisan dan Deret Aritmetika - Anggun Purnamasari; Widiawati Widiawati; Indah Widyaningrum (ARITHMETIC: Academic Journal of Math, 2020)
The purpose of this study was to determine the effects of the discovery learning model using Baretic Clock teaching aids on students' understanding of the concept of arithmetic sequences and arithmetic series in class XI SMA Negeri 4 Kota Pagar Alam for the 2019/2020 academic year. The research method used in this research is the experimental method in the category of Pre-Test Post-Test Only Control Design. The population in this study were students of class XI MIPA at SMA Negeri 4 Kota Pagar Alam. Meanwhile, the samples in this study were students of class XI MIPA 4 and XI MIPA 6, respectively 34 and 33 students. Data collection using documentation and test methods. After the data is collected, the normality and homogeneity test is carried out to find out the data to be analyzed comes from data that is normally distributed and homogeneous. From the results of this analysis, the data were processed based on the conceptual understanding indicator to determine the effect of the Discovery Learning model using baretic clock teaching aids on students' conceptual understanding. So the results of the study show that there is an effect of the Discovery Learning model using baretic clock teaching aids on students' conceptual understanding of the arithmetic sequence and series material for class XI SMA Negeri 4 Kota Pagar Alam for the 2019/2020 academic year